2005
DOI: 10.1016/j.neuroscience.2004.10.045
|View full text |Cite
|
Sign up to set email alerts
|

Effect of glutamine synthetase inhibition on astrocyte swelling and altered astroglial protein expression during hyperammonemia in rats

Abstract: Inhibition of glutamine synthesis reduces astrocyte swelling and associated physiological abnormalities during acute ammonium acetate infusion in anesthetized rats. We tested the hypothesis that inhibition of glutamine accumulation during more prolonged ammonium acetate infusion in unanesthetized rats reduces cortical astrocyte swelling and immunohistochemical changes in astrocytic proteins. Rats received a continuous i.v. infusion of either sodium acetate or ammonium acetate for 24 h to increase plasma ammoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
44
0
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(49 citation statements)
references
References 46 publications
4
44
0
1
Order By: Relevance
“…3,30 Thus, astrocytes may be another source of ROS/RNOS in the acutely hyperammonemic brain in vivo. In line with this, in vivo inhibition of glutamine synthetase prevents not only ammonia-induced astrocyte swelling 31 but also cerebral NO production 27 and protein tyrosine nitration. 32 Remarkably, ROS/RNOS produced by astrocytes can affect neuronal function.…”
Section: Discussionsupporting
confidence: 60%
“…3,30 Thus, astrocytes may be another source of ROS/RNOS in the acutely hyperammonemic brain in vivo. In line with this, in vivo inhibition of glutamine synthetase prevents not only ammonia-induced astrocyte swelling 31 but also cerebral NO production 27 and protein tyrosine nitration. 32 Remarkably, ROS/RNOS produced by astrocytes can affect neuronal function.…”
Section: Discussionsupporting
confidence: 60%
“…These results are promising for manipulating brain metabolism during hyperammonia since the evidence of glutamine playing a significant role in the development of HE is substantial [7][8][9][10][11][12][13] and animal studies points to a beneficial effect of inhibition GS by MSO. [17][18][19][20][21] In support of this, two recent reviews considered the potential use of MSO in patients with acute liver failure and limited treatment offers. 36,37 It seems unlikely, though, that MSO will be considered as a possible treatment for hyperammonemia in patients with chronic liver disease as convulsions have been observed in animals administered MSO 38,39 but the possibility of designing analogs of MSO that inhibit GS without having the undesired side effects produced by MSO should be considered.…”
Section: Discussionmentioning
confidence: 99%
“…MSO has been widely used as a GS inhibitor in astroglia in studies of hyperammonemia, memory consolidation, and seizures, and its effects can be counteracted by glutamine application (Bacci et al, 2002;Suarez et al, 2002;Gibbs and Hertz, 2005;Tanigami et al, 2005;Liang et al, 2006). One recent study has used MSO to examine the effect of inflammatory stimuli on activation of GS in astroglia and found that GS activation is related to glutamatergic receptor activation (Muscoli et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…This shuttle includes the uptake of excessive extrasynaptic glutamate and the production [via glutamine synthetase (GS)] and release from astroglia of glutamine, which is then taken up by neuronal elements to replenish the supply of glutamate (Zwingmann and Leibfritz, 2003;Hertz, 2004;Hertz and Zielke, 2004;Fonseca et al, 2005). A potent inhibitor of GS in astroglia is methionine sulfoximine (MSO), and its effects can be counteracted by glutamine application (Bacci et al, 2002;Blin et al, 2002;Suarez et al, 2002;Shin et al, 2003;Gibbs and Hertz, 2005;Tanigami et al, 2005;Liang et al, 2006). However, only one study has used MSO to investigate the involvement of astroglial GS in the effects of noxious stimuli on glutamatergic receptor-related events in astroglia (Muscoli et al, 2005), and no studies have tested its effects on central sensitization in functionally identified nociceptive neurons.…”
Section: Introductionmentioning
confidence: 99%